Tooth ARcademy: A mobile app for teaching and learning of oral histology - Nazlee Sharmin; Hady Abdallah; Elias Jirgees; Ava K. Chow (PLoS ONE, 2025)
m-Learning is gaining popularity in health professional education; however, reports on mobile apps targeting didactic teaching and learning are scarce, particularly in the context of health professional courses such as histology. Histology is an essential foundational component of dental and medical education. At the Mike Petryk School of Dentistry, University of Alberta, instructors utilize photomicrographs from textbooks to teach students on the microanatomy of teeth, the development of tooth and facial regions, and developmental anomalies. Limited availability of high-quality tissue sections and time constraints present challenges for both students and instructors. To provide students with an accessible collection of diverse histological sections and to facilitate in-class interactive didactic teaching, we developed an Augmented Reality (AR)-based mobile app called Tooth ARcademy. The development of Tooth ARcademy comprises the following steps: selecting histology glass slides, digitizing the glass slides, curating and annotating the digital slides, preparing multiple-choice questions, and integrating the resources into the mobile app. Tooth ARcademy is available worldwide at no cost. The app has three modes. Instructors can use the AR-based Learn mode to create in-class activities and supplemental questions tailored to students with specific learning outcomes. The Practice mode enables students to study oral histology outside of class time. With the Quiz mode of Tooth ARcademy, students can self-assess their knowledge of oral histology by participating in quizzes. The knowledge of oral histology is essential for dental education. Tooth ARcademy is designed to create interactive and engaging learning environments both inside and outside the classroom. Besides some limitations of the current phase, Tooth ARcademy can be a valuable m-learning tool that benefits students and educators in dental, medical, and other professional schools.